Overexpression of Tet3 in donor cells enhances goat somatic cell nuclear transfer efficiency. (8th June 2018) - Han, Chengquan; Deng, Ruizhi; Mao, Tingchao; Luo, Yan; Wei, Biao; Meng, Peng; Zhao, Lu; Zhang, Qing; Quan, Fusheng; Liu, Jun; Zhang, Yong
Abstract : Ten–eleven translocation 3 (TET3) mediates active DNA demethylation of paternal genomes during mouse embryonic development. However, the mechanism of DNA demethylation in goat embryos remains unknown. In addition, aberrant DNA methylation reprogramming prevalently occurs in embryos cloned by somatic cell nuclear transfer (SCNT). In this study, we reported that TET3 is a key factor in DNA demethylation in goat pre‐implantation embryos. Knockdown of Tet3 hindered DNA demethylation at the two‐ to four‐cell stage in goat embryos and decreased Nanog expression in blastocysts. Overexpression of Tet3 in somatic cells can initiate DNA demethylation, reduce 5‐methylcytosine level, increase 5‐hydroxymethylcytosine level and promote the expression of key pluripotency genes. After SCNT, overexpression of Tet3 in donor cells corrected abnormal DNA hypermethylation of cloned embryos and significantly enhanced in vitro and in vivo developmental rate ( P  <   0.05). We conclude that overexpression of Tet3 in donor cells significantly improves goat SCNT efficiency. Abstract : Ten–eleven translocation 3 (TET3) is a key factor in DNA demethylation in goat pre‐implantation embryos. Overexpression of Tet3 in donor cells could significantly improve goat somatic cell nuclear transfer (SCNT) embryonic developmental rates in vitro and improves goat SCNT efficiency.